Building a growth mindset : reframe challenges to thrive at work. (O'Reilly Media, Inc., 2023)
People want to thrive at work, which consumes so many of our waking hours.And yet they are often discouraged by setbacks and feel that they're just not smart enough to get ahead. In this course, you will learn that adopting a "growth mindset" can help reframe these unproductive ways of thinking, illuminate the upside of failure, and make you feel less stuck. You will also learn the important role that companies play in creating-or failing to create-an environment that nurtures a growth mindset. After this course, you will know the difference between a growth and fixed mindset and have several strategies in hand for pursuing growth at work and in your personal life. What you'll learn and how you can apply it The theory of a growth mindset and evidence supporting it How growth dovetails with or can become misaligned with the corporate good Barriers to the growth mindset and evidence about bureaucracy The most fertile corporate environments for growth and how to join them This course is for you because... You're curious about the notion of growth mindset and wondering if it can helpadvance your career. You're a manager or individual contributor curious about what a growth mindsetis and interested in furthering your career in a healthy corporate environment. Prerequisites: Prior knowledge from working at a business or corporation College or university education would be helpful.